Meat Handling Practices Among Retail Meat Shops in Dharan Sub-Metropolitan City - Subedi, Dinesh; Bhattarai, Tanka; Acharya, Dev Raj (Tribhuvan University Journal of Food Science and Technology, 2022)
The study was conducted to assess the status of sanitation and hygienic practices among retail meat shops in Dharan Sub metropolitan city. A total of 117 retail meat shops were randomly selected and interviewed by using a self-prepared semi-structured questionnaire. 98.3% of respondents were unaware of Slaughterhouse and Meat Inspection Act, 52.1% of the butchers didn’t wear an apron, 76.1% of butchers did not have an evisceration facility, antemortem and post mortem practices were rarely practiced and more than 80% did not use detergent-water for cleaning function. On a 21-point rating score for good hygienic practices, 41.88% of meat shop fell into the poorer category getting less than 45% score showing significant association (p<0.05) with the type of meat, sex of the worker and training received. General hygiene practices in most of the meat shop of Dharan have not been observed satisfactory. Since poorer meat handling practices are directly related to poorer meat quality, this study recommends immediate and effective intervention to ensure the quality and safety in the meat market of Dharan.